Evaluasi Program Pengendalian Hipertensi di Puskesmas Darul Imarah Kabupaten Aceh Besar 2022-2024 - Natha Bella; Sari Wartini; Putri Nur Ramadhani; Farrah Fahdhiene; Mutia Zahara (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
The hypertension control program at the Darul Imarah Community Health Center has been running continuously for the past few years as part of the promotive and preventive efforts in the primary health care system. An evaluation of the program implementation for the period 2022–2024 was conducted to assess the effectiveness and shortcomings of the program based on the IPO-OI (Input, Process, Output, Outcome, Impact) evaluation approach. This study used a descriptive method with a mixed approach, namely qualitative and quantitative, with data obtained through documentation studies of activity reports, field observations, and in-depth interviews with health workers and cadres directly involved in program implementation. The evaluation results show that in terms of input, the program has been supported by the availability of adequate human resources, operational budget support, blood pressure check facilities, regular cadre training, and internal regulations that support program implementation. The target coverage also continues to expand as the number of at-risk populations increases. The implementation process includes routine activities such as hypertension screening, recording and reporting cases, education through counseling groups, and community-based innovations such as the KEPAK (Kendalikan Penyakit Kronis) program, which has been proven to increase community participation. The resulting outputs include an increase in the number of registered hypertension patients from 2,800 in 2022 to 3,500 by the end of 2024, increased follow-up visits, and increased community engagement in the program. Outcomes are evident in the proportion of patients able to control their blood pressure, reaching 80%, and increased adherence to long-term treatment. Meanwhile, the impact of this program is increased public awareness of the dangers of hypertension, improved health literacy, and strengthened community-based primary healthcare systems. Overall, the evaluation results indicate that the hypertension control program at the Darul Imarah Community Health Center is effective and has the potential to be replicated in other areas.